Neutrophil-to-lymphocyte ratio (NLR) as a predictive index for liver and coagulation dysfunction in preeclampsia patients - Hui Xing Cui; Chen Chen; Young Mi Jung; Zhen Yi Guo; Chun Yu Dong; Seung Mi LEE; Yin Hua Zhang (BMC Pregnancy and Childbirth, 2023)
Abstract Background Pre-eclampsia (PE) is a pregnancy disorder that is related to an enhanced immune response. Immune cell characteristics such as neutrophil or monocyte to lymphocyte ratios (NLR, MLR) are known to be related to kidney and liver dysfunction in hypertensive patients. Here, we aimed to analyze the correlations between NLR, MLR and platelet to lymphocyte ratio (PLR) and liver, renal and coagulation functional parameters and the impacts of these immune cell profiles to the prognostic significance in PE patients. Methods Pre-delivery hematological and biochemical parameters of 320 first-time pregnant women registered at the Obstetrics Department of Yanbian University Hospital from 2016 to 2019 were analyzed retrospectively. Patients were divided into normal pregnancy (normal, n = 161), mild PE (mPE, n = 28) and severe PE (sPE, n = 131) groups according to diagnostic criteria. Pearson correlation analysis were performed and area under the curve (AUC) were conducted for the diagnostic values of NLR, MLR and PLR. Results were validated with data from the Department of Obstetrics and Gynecology of Seoul National University Hospital (SNUH). Results Kidney functional indexes were adversative in mPE and sPE and liver and coagulation indexes were worse in sPE compared to normal groups. Among immune cells, lymphocytes were increased in mPE and sPE patients, resulted in reduced NLR, MLR and PLR in PE groups, more significant difference were shown in sPE. NLR and PLR were associated with CREA and/or BUN negatively and positive associations were observed with total protein (TP) and albumin (ALB) in sPE. Only NLR showed positive associations with coagulation indexes (PT and APTT) in sPE. AUC analysis for NLR, MLR and PLR were 0.700, 0.656, 0.643, respectively, and NLR < 3.7 predicted hypertension (95% CI in all participants: 0.647–0.749, p < 0.001). Blood pressure, liver, kidney and coagulation indexes were worse at cut off value (NLR < 3.7), and this was validated with the data from SNUH. Conclusion NLR could be used as an independent predictor of liver and coagulation dysfunction in PE patients. Our results may provide non-invasive and efficient way of the risk assessment among PE patients.